The HABITAT project - Tam, Kristen (International Livestock Research Institute, 2024)
Smallholder pasture management plays an important role for biodiversity in Kenyan highlands. Smallholder farms account for 80 per cent of all farms in Kenya. However, trying to balance needs of both livestock, pastures, biodiversity and crops may lead to trade-offs between maximizing yields and providing natural habitats for flora and fauna. The current challenge is a lack of data on how smallholder pasture management affects biodiversity, and the potential trade-offs and synergies with climate resilience, greenhouse gas (GHG) emissions, and livestock productivity. This limits researchers and policymakers’ ability to provide management recommendations that are feasible for smallholders and help to protect the environment, or that help Kenya meet its national climate change, productivity, and biodiversity goals. But the situation is changing, as recently the Harnessing Pasture Biodiversity and Productivity (HABITAT) project received funding from the Global Centre for Biodiversity and Climate (GCBC) to study the effects of pasture management on GHG emissions, plant biodiversity and dairy production in smallholder farms in Bomet, Kenya.